1995
DOI: 10.1128/jvi.69.8.5033-5038.1995
|View full text |Cite
|
Sign up to set email alerts
|

Association of mouse fibrinogen-like protein with murine hepatitis virus-induced prothrombinase activity

Abstract: Previously, we demonstrated induction of a unique macrophage prothrombinase during infection of BALB/cJ mice by mouse hepatitis virus strain 3 (MHV-3). By immunologic screening, a clone representing this prothrombinase was isolated from a cDNA library and sequenced. The sequence identified this clone as representing part of a gene, musfiblp, that encodes a fibrinogen-like protein. Six additional clones were isolated, and one clone, p11-3-1, encompassed the entire coding region of musfiblp. Murine macrophages d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 27 publications
7
41
0
Order By: Relevance
“…No difference in expression of fgl-2 mRNA was detected between A59-DE-HE-and A59-DE-CAT-infected mice (data not shown). Histologic examination of the livers did not reveal coagulopathy typically induced by MHV-3 infection (Parr et al 1995).…”
Section: Fig 3ðcontinuedmentioning
confidence: 79%
See 1 more Smart Citation
“…No difference in expression of fgl-2 mRNA was detected between A59-DE-HE-and A59-DE-CAT-infected mice (data not shown). Histologic examination of the livers did not reveal coagulopathy typically induced by MHV-3 infection (Parr et al 1995).…”
Section: Fig 3ðcontinuedmentioning
confidence: 79%
“…To determine if the activation of the mouse fibrinogen-like protein (fgl-2) gene was associated with the fulminent hepatitis induced by ic infection with the A59-DE-CAT virus, as has been shown to be the case in the hepatitis induced by MHV-3 (Parr et al 1995), livers were examined for the presence of fgl-2 gene mRNA by RT±PCR. No difference in expression of fgl-2 mRNA was detected between A59-DE-HE-and A59-DE-CAT-infected mice (data not shown).…”
Section: Fig 3ðcontinuedmentioning
confidence: 99%
“…3 Especially important is that MHV-3 infection in susceptible BALB/cJ mice causes the de novo synthesis of a unique procoagulant fgl2 prothrombinase by macrophages. 2 The murine fgl2 gene has been cloned, sequenced, and characterized in this laboratory. 2,4,14,15 Recent sequential studies showed that the development of fulminant viral hepatitis always followed the same pattern: initiation by viral-induced up-regulation of the fgl2 prothrombinase…”
Section: Discussionmentioning
confidence: 99%
“…The 225 amino acids at the carboxyl end corresponds to the well-conserved fibrinogen-related domain. 2 The five potential glycosylation sites are conserved in the mouse and human proteins. A cDNA of HFGL2, encompassing the entire coding region, was cloned into pcDNA3.1-His and expressed as a fusion protein (phfgl2his) in CHO cells ( Figure 3B).…”
Section: Isolation and Characterization Of Hfgl2mentioning
confidence: 99%
See 1 more Smart Citation